2005
DOI: 10.1507/endocrj.52.551
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Carcinoma Associated with Graves' Disease

Abstract: This report concerns a 79-year-old woman with coexisting anaplastic thyroid carcinoma (ATC) and Graves' disease (GD). The patient was referred to our clinic because of palpitation and a palpable mass on the left side of her neck. Thyroid function tests showed hyperthyroidism with elevated thyroid-stimulating antibodies. Ultrasonography of the thyroid demonstrated an adenomatous nodule-like marcated nodule (27.6 x 26.5 x 36.4 mm) with cystic degeneration inside the left lobe. (123)I thyroid scintigraphic imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
7
1
1
Order By: Relevance
“…For thyroid cancer, previous studies have reported inconsistent results (Cole, 1991;Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). We found increased risks, confined to the early overall Cancer risk after Graves' disease X Shu et al follow-up period, though for men the risk was noted even for the All1 þ period.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…For thyroid cancer, previous studies have reported inconsistent results (Cole, 1991;Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). We found increased risks, confined to the early overall Cancer risk after Graves' disease X Shu et al follow-up period, though for men the risk was noted even for the All1 þ period.…”
Section: Discussioncontrasting
confidence: 54%
“…Inconsistent associations between GD and malignant tumours have been reported (Cristofanilli et al, 2005;Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). Small study size and variable case reporting weaken the generalisability of the results (Majima et al, 2005;Pazaitou-Panayiotou et al, 2008). In our cohort study, the largest to date, 18 156 hospitalised GD patients were studied to quantify their subsequent cancer risk.…”
mentioning
confidence: 88%
“…Although it has been widely accepted that RAI is safe, some studies have suggested that RAI therapy is possibly associated with a small increased risk of thyroid cancer [2-4]. DeGroot [5] reported that the RAI treatment can induce an increase of thyroid antibodies, such as TSH receptor antibody, and it was suggested that thyroid stimulating antibodies play an important role in thyroid carcinogenesis [6,7]. These antibodies also can stimulate angiogenesis, which contributes to thyroid tumor cell growth, by activating vascular endothelial growth factor [8].…”
Section: Discussionmentioning
confidence: 99%
“…The term "anaplastic pseudothyroiditis" is also still in use. 11 This phenomenon is pathophysiologically interesting because it 10 Given that tumor destruction is the cause of hyperthyroidism in these patients, the use of antithyroid drugs and radioiodine therapy has no effect because there is no increased production of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite multimodal therapeutic approaches (surgery, radiotherapy, and chemotherapy), prognosis is still poor with mean survival between 3 and 6 months. [3][4][5][6][7][8][9][10][11][12] In our Center, ATC was diagnosed in 126 patients in the period between 1993 and 2005. It accounts for 2% of all thyroid malignancies.…”
Section: Learning Objectivesmentioning
confidence: 99%